PENGARUH KEPRIBADIAN PRESIDEN JOKOWI DALAM KEBIJAKAN LUAR NEGERI INDONESIA: STUDI KASUS PELANGGARAN CINA DI NATUNA - Putra, Tomy Darma; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
South China Sea dispute is a complicated problem faced by ASEAN countries. Through the Nine Dash Line, China claims that the South China Sea still as its territory. China takes action by militarizing the islands in it. Even though Indonesia is not included in the disputes, it turns out that Natuna waters overlap with the Nine Dash Line owned by China. These problems had caused tensions between the two countries because China had intervened in law enforcement efforts carried out by Indonesian patrol vessels against Chinese fishing vessels that violated Indonesia’s sovereignty. This study will explain the behavior of Indonesia in the dispute. Using the idiosyncratic approach, this study analyzes the political leader, Jokowi, specifically his personal character. This study will use content analysis that focus on Jokowi's statements on the dynamics of the South China Sea dispute and his response to sovereignty violation by China. The results of this study show that there are similarities in Jokowi’s behavior patterns since he was a mayor in responding to a problem. In response to China, Jokowi has character of high nationalism, high need of power, high belief in control over event, low conceptual complexity, and low distrust to other.